Occupational Licensing Reform: A Step-by-Step Approach for Pharmacy Licensing Boards - Alex Adams (INNOVATIONS in Pharmacy)
Occupational licensing reform is essential but challenging for state agencies. This paper presents a step-by-step framework for pharmacy licensing boards, inspired by the Idaho State Board of Pharmacy’s (BOP) efforts, which achieved a 51.2% reduction in regulatory word count and a 75% cut in page count. By establishing baselines, prioritizing reform areas, and setting clear reduction goals, the BOP streamlined licensing, modernized professional practice standards, and adopted technology-agnostic facility regulations. The transition to enforcement-centric accountability ensured public safety while fostering innovation and economic growth. Early results include increased pharmacy services, improved access, and significant industry investments. This framework offers a replicable approach for other licensing boards to reduce red tape, support economic growth, and enhance regulatory efficiency without compromising health and safety.